Benzyl butyl phthalate non-linearly affects rat Leydig cell development during puberty. (10th October 2019) - Lv, Yao; Dong, Yaoyao; Wang, Yiyan; Zhu, Qiqi; Li, Linxi; Li, Xiaoheng; Lin, Zhenkun; Fan, Lihua; Ge, Ren-Shan
Graphical abstract: Highlights: Benzyl butyl phthalate stimulates immature Leydig cell proliferation. Benzyl butyl phthalate increases Leydig cell number. Benzyl butyl phthalate inhibits androgen production at the high dose. Benzyl butyl phthalate is metabolized into mono-benzyl phthalate that has potent toxicity. Abstract: Benzyl butyl phthalate (BBP) is a widely used plasticizer and has raised public health concerns. Here, we report the effects of BBP on the testis development during rat puberty. BBP (0, 10, 100 or 1000 mg/kg) was gavaged to 35-day-old male Sprague Dawley rats for 21 days. The serum testosterone levels, Leydig cell number, the expressions of Leydig and Sertoli cell genes and proteins were measured. The in vitro effects on steroidogenesis and gene expression in immature Leydig cells were observed. BBP significantly increased serum testosterone level at 10 mg/kg but lowered its level at 1000 mg/kg without affecting serum luteinizing hormone and follicle-stimulating hormone levels. BBP increased Leydig cell number at all doses but inhibited steroidogenic capacity per Leydig cell at 1000 mg/kg. BBP significantly increased the ratio of phosphos-AKT2 (pAKT2)/AKT2, and phosphos-ERK1/2 (pERK1/2)/ERK1/2 in the testis. Mono-benzyl phthalate (the metabolite of BBP) inhibited steroidogenesis but BBP did not affect androgen production in immature Leydig cells in vitro. In conclusion, BBP non-linearly regulates Leydig cell development by increasing Leydig cell number but inhibiting steroidogenesis.